2023
DOI: 10.1073/pnas.2220021120
|View full text |Cite|
|
Sign up to set email alerts
|

High-throughput experimentation for discovery of biodegradable polyesters

Katharina A. Fransen,
Sarah H. M. Av-Ron,
Tess R. Buchanan
et al.

Abstract: The consistent rise of plastic pollution has stimulated interest in the development of biodegradable plastics. However, the study of polymer biodegradation has historically been limited to a small number of polymers due to costly and slow standard methods for measuring degradation, slowing new material innovation. High-throughput polymer synthesis and a high-throughput polymer biodegradation method are developed and applied to generate a biodegradation dataset for 642 chemically distinct polyesters and polycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Here, aliphatic condensation polymers are expected to have higher susceptibility to biodegradation compared to aromatic ones. 60,61 For preliminary evaluation of the susceptibility of our aliphatic PU networks to biodegradation, all synthesized aliphatic PU networks with different crosslinking degrees were subjected to enzymatic degradation assays in aqueous solution using Candida rugosa lipase and lipase from Aspergillus niger as enzymes. These enzymes have been commonly used to evaluate the enzymatic degradability of polyesters, polyurethanes and polyester-urethanes.…”
Section: Resultsmentioning
confidence: 99%
“…Here, aliphatic condensation polymers are expected to have higher susceptibility to biodegradation compared to aromatic ones. 60,61 For preliminary evaluation of the susceptibility of our aliphatic PU networks to biodegradation, all synthesized aliphatic PU networks with different crosslinking degrees were subjected to enzymatic degradation assays in aqueous solution using Candida rugosa lipase and lipase from Aspergillus niger as enzymes. These enzymes have been commonly used to evaluate the enzymatic degradability of polyesters, polyurethanes and polyester-urethanes.…”
Section: Resultsmentioning
confidence: 99%
“…Reineke and co-workers reported the synthesis and polymerization of a novel disubstituted valerolactone, β-acetoxy-δ-methyl­valerolactone, which was derived from the renewable feedstock triacetic acid lactone (TAL). The ROP thermodynamic behavior was examined, and the resultant amorphous material displayed a T g of 25 °C (Table , run 15). Li et al prepared a series of poly­(ester–amide)­s (PEAs) by the ROP of morpholino-2,5-dione derivatives (MDs), which can be synthesized from α-hydroxy acids and α-amino acids. , These amorphous PEAs can also be directly depolymerized to pristine MDs under an amberlyst 15 ion-exchange resin.…”
Section: Closed-loop Recyclable Polyestersmentioning
confidence: 99%
“…The heteroatom substitutions in the main chain can affect the polarity, crystallinity, mechanical properties and chemical recyclability of polyesters . Recently, the incorporation of heteroatoms into the polymer backbone has become an efficient tool to accelerate degradation and construct chemical recyclable polyesters .…”
Section: Closed-loop Recyclable Polyestersmentioning
confidence: 99%
See 1 more Smart Citation
“…High-throughput experimentation (HTE) platforms and workflows in material science can help to discover new materials and widen the field of applications of polyolefins. In a recent paper, a multidisciplinary high-throughput approach covering the entire chain of knowledge, was introduced to build sound and reliable databases for quantitative structure–property relation (QSPR) investigations and to prepare new materials. , In particular, it was demonstrated that HTE protocols implemented for the high-temperature and high-pressure synthesis of statistical multiblock copolymers (MBCs) with chain shuttling copolymerization (CSC) technology allow the production of MBCs, mimicking the commercial Dow INFUSE materials in all industrially relevant aspects.…”
Section: Introductionmentioning
confidence: 99%